Bacterial Diversity in Sustainable Agriculture - Maheshwari, Dinesh K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Diversity exists among all kinds of microorganisms. As evolution preceded new kinds of microorganisms appeared. The structural, functional and genetic diversity of any cell represents its evolutionary event.  Both culturable and non-culturable (metagenomic) bacteria play a significant role in human welfare. They have multifarious functions, as effective as other synthetic agents applied in agro-ecosystem. The various facets of bacterial diversity are presented in relation to their emergence in agriculture in this volume entitled “Bacterial Diversity in Sustainable Agriculture”.
Preface -- 1. Trends and Prospects of Microbial Diversity in Rhizosphere; Dinesh Kumar Maheshwari, Shrivardhan Dheeman -- 2. Diversity Utility and Potential of Actinobacteria in the Agro-Ecosystem; Govindan Selvakumar et al -- 3. Diversity of plant associated Actinobacteria; Bouizgarne Brahim, Ait Ben Aouamar -- 4. Root Nodules of Legumes Growing in Arid to Semi-Arid African Soils and other Areas of the World; Flora Pule-Meulenberg -- 5. Genetic Diversity of Soybean Root Nodulating Bacteria; David Biate et al -- 6. Diversity and Function of Bacterial Assemblages in Savanna Vegetation Soils; Elisa Catão Caldeira Pires et al -- 7. Diversity of Plant-Growth-Promoting Rhizobacteria Associated with Maize (Zea mays L.); Letícia Arruda et al -- 8. Transgenic Cotton and its Impact on Microbial Diversity; Kulandaivelu Velmourougane, D. Blaise -- 9. Microbial and Functional Diversity of Vermicompost Bacteria; Jayakumar Pathma, Natarajan Sakthivel.-10. Diversity of Cold Tolerant Phosphate Solubilizing Microorganisms from North Western Himalayas; Piyush Joshi et al -- 11. Osmotolerant Microbial Resources of Saline Ecologies of India: Dynamics and Potential; Jayashree Rath, T.K. Dangar -- 12. Culture Independent Diversity Analysis of Soil Microbial Community and Their Significance; Bidisha Sharma et al -- 13. The Importance and Application of Bacterial Diversity in Sustainable Agricultural Crop Production Ecosystems; Noah Rosenzweig -- Index.
Keywords: Biodiversity; Conservation biology; Ecology .; Microbial ecology; Plant systematics; Plant taxonomy; Microbial genetics; Microbial genomics; Biodiversity; Conservation Biology/Ecology.; Microbial Ecology; Plant Systematics/Taxonomy/Biogeography.; Microbial Genetics and Genomics